Interventions to improve awareness and reduce the stigma associated with neurodegenerative conditions in minority ethnic communities: A scoping review protocol - Maria Caulfield; Sahdia Parveen; Matthew Prina; Jan R Oyebode; Karen Windle; Catherine Charlwood; Adelina Comas-Herrera; Catherine Quinn; Linda Clare (PLoS ONE, 2025)
Objective This scoping review aims to identify interventions aiming to improve awareness of and reduce stigma related to neurodegenerative conditions within South Asian and Black (African-Caribbean, African, African American, Black British) communities with a focus on synthesising the methods employed for culturally tailoring interventions. Introduction Minority ethnic communities affected by neurodegenerative conditions often face health and social care disparities. This can lead to delayed diagnosis and poor health outcomes. Interventions that provide relevant, accessible information about neurodegenerative conditions may help reduce disparities in care access. There is limited knowledge about the methods used to culturally tailor interventions for minority ethnic communities and their efficacy. Inclusion criteria Eligible sources will include interventions specifically tailored for South Asian and Black communities, living with dementia, Parkinson’s disease, Huntington’s disease, or motor neurone disease. Interventions must be conducted in countries that are member states of the Organisation for Economic Co-operation and Development where these two groups constitute minority populations and are likely to face inequalities in care access. Methods A scoping review guided by the Joanna Briggs Institute Manual for Evidence Synthesis will be conducted. Searches of Medline (EBSCO), APA PsycInfo (EBSCO), and EMBASE (Elsevier) will be conducted. Study selection will be based on 100% agreement between two reviewers. Data will be extracted, charted, and summarised narratively followed by consultation with stakeholders. Implications This review will identify culturally sensitive strategies for raising awareness and reducing the stigma associated with neurodegenerative conditions among South Asian and Black communities within the Organisation for Economic Co-operation and Development countries. By utilising these inclusive approaches, communities may feel more empowered to seek a diagnosis for symptoms and live better with the condition. The findings of this review will be shared with the public and policymakers to promote awareness and evidence-based policy making.